2011
DOI: 10.1007/s10211-011-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Foraging and vigilance time allocation in a guanaco (Lama guanicoe) population reintroduced in Quebrada del Condorito National Park (Córdoba, Argentina)

Abstract: In reintroduction projects, ethology studies play a significant role in evaluating the behaviour of the individuals in habitats where they are reintroduced. We studied foraging and vigilance time allocation of a guanaco (Lama guanicoe) population reintroduced in Quebrada del Condorito National Park (QCNP), in the central mountains of Córdoba, Argentina. On average, individuals showed a higher proportion of time invested in vigilance and a lower proportion of time invested in foraging than a previously studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In both Phase 1 and 2 of this study the alpacas spent limited time (0.8%) displaying 'alert' behaviours and it is noted that only a single fox was observed on one occasion during the study. Previous research suggests that alert behaviours displayed by alpacas are likely to be opportunistic towards threats in their environment, as has been researched in other related species such as guanacos [47]. As there was only a single observed threat over the observation days of this work, it is likely that the alpacas did not have motivation to exhibit a high level of alert behaviour during the day.…”
Section: Daily Alpaca Behavioursmentioning
confidence: 64%
“…In both Phase 1 and 2 of this study the alpacas spent limited time (0.8%) displaying 'alert' behaviours and it is noted that only a single fox was observed on one occasion during the study. Previous research suggests that alert behaviours displayed by alpacas are likely to be opportunistic towards threats in their environment, as has been researched in other related species such as guanacos [47]. As there was only a single observed threat over the observation days of this work, it is likely that the alpacas did not have motivation to exhibit a high level of alert behaviour during the day.…”
Section: Daily Alpaca Behavioursmentioning
confidence: 64%
“…Contrary to our predictions, group cohesion and vigilance were not affected by the chulengo/adult ratio, despite chulengos being the preferred prey. These results could be related to the low time allocated to vigilance by females in family groups, in which the male is the main vigilant (Barri & Fernández, ; Marino & Baldi, ). Finally, we did not detect differences in guanaco grouping behavior associated with their location within or outside Torres del Paine National Park.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, some management decisions, such as the absence of a pre-adaptation period in the first released groups, reduced the total number of established individuals [ 28 ]. Nevertheless, different studies conducted on the guanaco population reintroduced in QCNP indicated that the individuals that survive the critical post-release stage were adapted in terms of behaviour [ 25 ], habitat selection [ 26 ], and diet [ 27 ]. Preliminary evidence shows that the guanacos could contribute to the ecological restoration of the area (unpublished data), reinforcing the importance of this project focused on restoring natural processes rather than addressing only extinction risk [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, 113 individuals from a wild northern Patagonia population (40° 47'S, 66° 45'W) were released without being subject to a pre-adaptation period, of which 19 females and 17 males were radio- collared. Of all individuals released in 2007, only about 20% survived the first three months of the critical post-release period, with starvation and predation by puma ( Puma concolor ) being the most frequent causes of death [ 25 ]. In 2011, 25 individuals from a captive population from Buenos Aires (38°01'S, 61°40'W) were released; of these individuals, five females and two males were radio- collared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation